Transformation of Assessment in Teaching English at Higher Education: Leveraging Quizizz to Enhance Student Participation and Motivation - Ridhwan, M. (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2023)
This qualitative case study delves into the transformative potential of integrating Quizizz, an interactive assessment tool, within the realm of English language instruction for novice students enrolled in the Islamic Education Department at STAI Auliaurrasyidin. Employing purposive sampling and thematic analysis, the research uncovers a notable shift in student engagement, motivation, and language proficiency. The study's outcomes underline Quizizz's gamified approach as a pivotal catalyst in redefining the assessment landscape, igniting a renewed enthusiasm for learning, and fostering an active and participatory classroom environment. The study reveals that Quizizz's gamified platform ignites student motivation and engagement, bridging the gap between apprehension and enthusiasm. Multiple-choice questions, a core feature of Quizizz, are particularly effective in overcoming novice language learners' challenges with open-ended queries. Classroom observations highlight the heightened sense of participation and active engagement during evaluations, fostering a dynamic learning environment. The implications extend beyond language instruction, resonating with the broader goals of holistic education and offering insights for enhancing pedagogical practices in Islamic studies and other disciplines.